Goering, Nelson. 2023. Prosody in Medieval English and Norse. Oxford: Oxford University Press. Pp. xiii + 375. ISBN 9780197267462. - Males, Mikael (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2024)
Book review of Goering, Nelson. 2023. Prosody in Medieval English and Norse. Oxford: Oxford University Press. Pp. xiii + 375. ISBN 9780197267462.